Radial solutions for Hénon type fully nonlinear equations in annuli and exterior domains - Maia, Liliane; Nornberg, Gabrielle (Mathematics in engineering, 2022)
In this note we study existence of positive radial solutions in annuli and exterior domains for a class of nonlinear equations driven by Pucci extremal operators subject to a Hénon type weight. Our approach is based on the shooting method applied to the corresponding ODE problem, energy arguments, and the associated flow of an autonomous quadratic dynamical system.